Transformasi Keagamaan dan Sosial dalam Komunitas Ṭarīqah Qādiriyyah Naqshabandiyyah di Purwosari, Lampung Tengah - Ahmad Mukhlishin; Jauharotun Nafisah; M. Muslih; Annida Ayu Damaro; Deby Setia Negara; Tristi Monita; Afika Duri (Bulletin of Indonesian Islamic Studies, 2024)
This study explores the religious and social transformation within the Ṭarīqah Qādiriyyah Naqshabandiyyah (TQN) community of Roudlotus Solihin in Purwosari, Lampung Tengah. Using a qualitative case study approach, the research is grounded in Anthony Giddens’s theory of structuration and Pierre Bourdieu’s theory of practice. Data were collected through in-depth interviews and participant observation involving religious leaders (mursyid) and ordinary members. The findings reveal that the community has undergone significant transformation both in spiritual practices and social engagement. Regular religious activities—such as dzikr assemblies, haul celebrations, and routine pengajian—have expanded to include social empowerment programs and digital outreach through social media. These practices strengthen internal solidarity and promote broader social interaction. Moreover, generational differences are managed through inclusive strategies that integrate youth participation and technological innovation without abandoning the core spiritual doctrines. The study concludes that the TQN community in Purwosari acts as both a religious institution and a social agent, capable of reinterpreting its traditions to address contemporary challenges. This research contributes to the broader discourse on Indonesian Islam by showing how local Sufi communities sustain religious authority while engaging in meaningful social transformation.